1980
DOI: 10.1530/acta.0.0940117
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of puberty in boys with delayed puberty by clomiphene citrate. A clinical and laboratory study

Abstract: Clomiphene citrate was administered at a dose of 50 mg/day for 3 months to 29 boys with delayed puberty, 15 in a stage of early puberty (group 1) and 14 in stages of mid puberty (group 2). In both groups a significant acceleration in the advancement of pubertal signs was noted in the 6-month period following initiation of therapy as compared to a non-treated control group. A significant rise in the mean (\m=+-\SD) basal plasma LH levels, from 1.0 \m=+-\0.4 to 2.7 \ m=+-\2.2 mU/ml in group 1 (P< 0.05) and from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…[17] Although, as acceleration of puberty in 29 boys with delayed puberty were treated with CC 50 mg/day for 3 months, CC therapy caused a rise in T level in the treatment groups. [18] Another increased of T level were found as a result of oral administered of CC 25mg/day for male testosterone deficiency. [19] On other hand in women CC treatment showed a reverse result to the present study as where confirmed reported increases in FSH and LH levels several days after CC administration.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 97%
“…[17] Although, as acceleration of puberty in 29 boys with delayed puberty were treated with CC 50 mg/day for 3 months, CC therapy caused a rise in T level in the treatment groups. [18] Another increased of T level were found as a result of oral administered of CC 25mg/day for male testosterone deficiency. [19] On other hand in women CC treatment showed a reverse result to the present study as where confirmed reported increases in FSH and LH levels several days after CC administration.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencesmentioning
confidence: 97%